PERAN BRAND IMAGE MEMEDIASI PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA SERUM AVOSKIN DI KOTA DENPASAR - Cresentia Godeliva Yevtatianti; Tjokorda Gde Raka Sukawati (Adisam Publisher, 2025)
The rapid growth of the skincare industry has created increasingly fierce competition among brands, especially in the facial serum category. Consumers, who are faced with a wide variety of serum brands, certainly have various considerations when making purchasing decisions. Avoskin, a well-known local skincare brand, faces challenges in increasing purchasing decisions despite continuing to carry out various promotions to keep its products competitive and the consumers' choice. Avoskin serum sales have experienced fluctuations that tend to decline. This study aims to analyse the role of brand image in mediating the influence of promotions on purchasing decisions for Avoskin serum in Denpasar City. The method used is non-probability sampling with purposive sampling technique. Data collection was conducted through a survey using a questionnaire distributed to 130 respondents. The analysis technique used was path analysis, followed by a Sobel test. The results of the analysis indicate that promotions have a positive and significant influence on purchasing decisions, promotions have a positive and significant influence on brand image, brand image has a positive and significant influence on purchasing decisions, and brand image is able to mediate the influence of promotions on purchasing decisions. The theoretical implications of this study support the findings of previous studies. The practical implications of this study provide a reference for Avoskin's management in their efforts to improve purchasing decisions. This can be achieved by paying attention to promotion and brand image.